2017
DOI: 10.18051/univmed.2017.v36.25-33
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside increases aquaporin-3 protein expression in the cytoplasm of normal human epidermal keratinocytes

Abstract: <p>Introduction<br />Skin hydration decreases with aging. Aquaporin-3 (AQP3) is a major protein that plays a role in skin hydration, therefore it is a novel target for skin moisturizing treatment. Retinoic acid (RA) as a well-known active agent in antiaging treatment increases AQP3 expression, but frequently causes harmful side effects. Asiaticoside, a saponin compound isolated from Centella asiatica (CA) is also known as an antiaging cosmetic and plays a role in wound healing. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…A similar pattern was previously shown in other studies with other moisturizing ingredients [17]. Although the mechanism by which the ingredient increases skin hydration is unknown, it may be due in part to the ability of one of the tested ingredient's components, asiaticosides, to increase the expression of Aquaporin-3 (AQP3) [28]. AQP3 is an important protein that plays a key role in skin hydration [29].…”
Section: Discussionsupporting
confidence: 78%
“…A similar pattern was previously shown in other studies with other moisturizing ingredients [17]. Although the mechanism by which the ingredient increases skin hydration is unknown, it may be due in part to the ability of one of the tested ingredient's components, asiaticosides, to increase the expression of Aquaporin-3 (AQP3) [28]. AQP3 is an important protein that plays a key role in skin hydration [29].…”
Section: Discussionsupporting
confidence: 78%
“…Currently, many studies are investigating the active compounds that increase AQP-3 expression levels, to enable the treatment of skin disorders. Many studies have reported plant-derived substances such as green Coffee arabica seed oil extract ( Del Carmen Velazquez Pereda et al, 2009 ), trans-zeatin purified from Zea mays ( Yang et al, 2009 ), Piptadenia colubrina extract ( Del Carmen Velazquez Pereda et al, 2009 ), and asiaticoside, isolated from Centella asiatica ( Wijayadi and Darmawan, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…asiatica extract with 3.2% concentration is used in the formulation. The reference of concentration base of the journal from Linda Yulianti W, et al 2017 [3] was mentioned that in 1 mg/ml asiaticoside can give the best result of hydrating/moisturizing. Chia seed oil in formulation performed with different concentrations (1%, 2%, 3%, and 4%), the concentration based on reference [13] that mentioned with 4% chia seed oil extract can give the best result of hydrating/moisturizing.…”
Section: Formulation and Evaluation Of Nanoemulsion Serum Productmentioning
confidence: 99%
“…Moisturizer product content ingredients capable to moisturize are occlusive, humectant, emollient, and protein rejuvenator [2]. C. asiatica had functioned and was reported as a protein rejuvenator because containing some natural compounds such as asiaticoside that can enhance the AQP3 expression in NHEKs (Normal Human Epidermal Keratinocytes) [3]. The natural product having the characteristic as an emollient is Chia seed oil (Salvia hispanica L.) which contains omega 3 [4].…”
Section: Introductionmentioning
confidence: 99%